Molecular Characterization Reveals Genetic Differences Between Wild and Captive Populations of Mandiangin Giant Gourami (Osphronemus goramy) - Agus Nuryanto; Maria Bramasti Susilo; Adi Amurwanto (Jurnal Biodjati, 2019)
Captive population of Mandiangin giant gourami (Osphronemus goramy Lac.) is a new strain developed from wild pop-ulations in Riam Kanan Dam. No much is known about the genetic constituent of this strain compared to the parental population. This re-search was done to obtain information whether genetic alteration has occurred in captive population compared to their wild parental pop-ulation. Wild population was caught from Riam Kanan Dam, while captive population was collected from Balai Perikanan Budidaya Air Tawar (BPBAT) “Freshwater Aquaculture Centre” Mandiangin, South Kalimantan. The captive population of Batanghari strain from BPBAT Sungai Gelam, Jambi was also analyzed. Molecular assess-ment was done using CO1 PCR-RFLP which was developed by digest-ing the amplicon of the CO1 gene from all populations using two re-striction enzymes, namely HindIII and TaqI and resulted CO1-HindIII and CO1-TaqI RFLP markers. All tested populations showed uniform patterns of those CO1-RFLP markers but with different fragment sizes among populations. This means all resulted RFLP markers were mono-morphic in each populations but polymorphic among giant gourami populations. In other words, no genetic diversity within population but substantial genetic differences was observed between wild and cap-tive Mandiangin populations. This proved that genetic alteration has occurred in Mandiangin captive populations compared to the wild pa-rental giant gourami population. In conclusion, captive and wild pop-ulations of Mandiangin giant gourami were genetically different. This result is vital as scientific base for future development of inland fish-eries, especially for breeding strategy of Mandiangin giant gourami.